Collaboration Strategy for Building Village Communities through Economic Empowerment in BUMDes Business Units - Purnomo, Sigit; Darwin, Muhadjir; Abdullah, Irwan; Susilastuti, Dewi Haryani (Interdisciplinary Social Studies, 2023)
Background: The Law on Villages mandates that the nature of village development is as an effort to improve the quality of life for the maximum welfare of the village community. It indicates that village development must involve village communities in an empowerment pattern. Aim: This study aims to determine the role of collaborating stakeholders in the community empowerment for the economic welfare of the Panggungharjo village, identify the implementation of community empowerment as a basis for improving the community’s economy through BUMDes there, and identify the success level of collaboration in economic empowerment as a strategy to build excellent and sustainable village communities there. Method: The research employed qualitative approach with descriptive methods. The data collection methods was interview with informants in Panggungharjo Village and documentation. Findings: The collaborative role of stakeholders in community empowerment can encourage the successful management of BUMDes and improve the economic welfare of the village. The implementation of community empowerment as a basis for increasing the community’s economy through BUMDes in the village has involved community participation to become actors in BUMDes activities, in which the community involvement is substantial in all BUMDes business units. The collaboration in economic empowerment within BUMDes forum can be successful based on the achievements of BUMDes, namely the rapid increase in Village Locally-Generated Income (PAD) and the income of BUMDes which is consistently increasing, the number of business units in the BUMDes has grown, and the number of BUMDes business units has increased people’s income and absorb workforce.